Sentiment analysis on Malaysian political issue on Twitter / Wan Muhammad Afif Zuraidi - Zuraidi, Wan Muhammad Afif (2022)
The increase of issues in Malaysia is happening recently with the covid-19 outbreak adding fuel to the fire. Furthermore, today when everyone has the luxury to go online and see news and share their thought in social media creates which created a platform for them to do so. This results in a lot of people sharing their sentiment about a certain issue. This research aims to analyse the sentiments of people on Malaysian political issues.